Technicalities in scientific communication: Analysis of the dissemination strategies used by the SINC Agency in the information published on its Twitter profile (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
One of the main challenges of the professional specialized in scientific communication is to ensure that the lay audience understands the scientific-technological terminology. Hence, the objective is to analyze the techniques implemented to insert the reformulation process (explanation or clarification) of technical terms in the informative pieces. This study's methodology analyzes the information published over a three-month period in @agencia_sinc (from November 16 to February 16). The conclusion is an offer to update these valuable techniques for active communication professionals and their implementation in the academic sector.